2008
DOI: 10.1002/joc.1713
|View full text |Cite
|
Sign up to set email alerts
|

Climate‐based sensitivity of air quality to climate change scenarios for the southwestern United States

Abstract: ABSTRACT:The need to understand future trends in air quality is an issue that is frequently raised by air quality planners and managers. The potential for extreme events is of particular interest, but forecasts are difficult using traditional methods and further complicated by predictions of future climate change. This study aims to address this research need through a climate-based sensitivity study of ground-level ozone and particulate matter (PM) in the U.S. Southwest. Extreme value methods were used to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 31 publications
(38 reference statements)
1
21
0
Order By: Relevance
“…This study builds on an earlier analysis that had suggested that climate change could have little net effect on PM concentrations because the net effect of increased particle production rates with higher temperature and particle concentration reductions associated with greater volatility would cancel one another out (Aw and Kleeman 2003). An analysis of ozone and particulate matter concentrations in Arizona under changing climatic conditions predicted similar results-an increase in ozone concentrations, but uncertainty in the effect on PM (Wise 2009 …”
Section: Particulate Mattersupporting
confidence: 62%
“…This study builds on an earlier analysis that had suggested that climate change could have little net effect on PM concentrations because the net effect of increased particle production rates with higher temperature and particle concentration reductions associated with greater volatility would cancel one another out (Aw and Kleeman 2003). An analysis of ozone and particulate matter concentrations in Arizona under changing climatic conditions predicted similar results-an increase in ozone concentrations, but uncertainty in the effect on PM (Wise 2009 …”
Section: Particulate Mattersupporting
confidence: 62%
“…SDSM has been widely applied in SD studies for both climate variables and air quality variables (Diaz-Nieto and Wilby, 2005;Dibike and Coulibaly, 2005;Khan et al, 2006;Wetterhall et al, 2006;Gachon and Dibike, 2007;Prudhomme and Davies, 2009;Wise, 2009;and others), and has been recommended by the Canadian Climate Impacts and Scenarios (CCIS) project (http://www.cics.uvic.ca).…”
Section: Introductionmentioning
confidence: 99%
“…Demuzere and van Lipzig (2010a) provide an overview of the many different approaches to statistical downscaling. These approaches are easily implemented, computationally inexpensive, and flexible, but are predicated on the assumption that the current climate statistical relationships between predictors and predictands will remain valid in a future climate, and the assumption of no change in emissions, transport or chemical formation processes (Demuzere and van Lipzig, 2010a, b;Timbal et al, 2009;Wise, 2009). In dynamical downscaling, global scale climate information at a coarse resolution is used to drive a higher resolution regional model which is run over a limited area, and may involve General Circulation Models (GCMs; resolution of a few hundreds of kilometers), global Chemical Transport Models (CTMs), Regional Climate Models (RCMs; resolution of a few tens of kilometres, simulating up to a single continent) and regional CTMs.…”
mentioning
confidence: 99%
“…The impact of future climate change on PM 2.5 is an emerging area of study (Liao et al, 2006Racherla and Adams, 2006;Tagaris et al, 2007Tagaris et al, , 2008Avise et al, 2009;Wise, 2009), with most studies reporting increases in aerosol species components or aerosol burden (cf. Liao et al, 2006).…”
mentioning
confidence: 99%